Peer pressure and adolescent mobile social media addiction: Moderation analysis of self-esteem and self-concept clarity - Xu, Xiaopan; Han, Wanqu; Liu, Qingqi (Frontiers in Public Health, 2023)
Social media addiction has increasingly been a critical social problem. We explored the association between peer pressure on mobile phone use and adolescent mobile social media addiction and tested whether self-esteem and self-concept clarity could buffer the effect of peer pressure. 830 adolescents (Mage = 14.480, SDage = 1.789) participated in our anonymous survey. The results showed that peer pressure significantly predicted adolescent mobile social media addiction. Self-esteem moderated the effect of peer pressure on mobile social media addiction in that peer pressure had a weaker effect for adolescents with higher self-esteem. Self-concept clarity moderated the effect of peer pressure on mobile social media addiction in that peer pressure had a weaker effect for adolescents with higher self-esteem. The two moderators also interact in that the moderation of self-esteem was stronger for adolescents with higher self-concept clarity and the moderation of self-concept clarity for adolescents with higher self-esteem. The results highlight the critical role of self-esteem and self-concept clarity in buffering the impact of peer pressure on mobile social media addiction. The findings promote a better understanding of how to buffer the undesirable effect of peer pressure and reduce the risk of mobile social media addiction among adolescents.